Global, regional, and national burden of heart failure and its underlying causes, 1990–2021: results from the global burden of disease study 2021 - Jun Ran; Ping Zhou; Jinxi Wang; Xuemei Zhao; Yan Huang; Qiong Zhou; Mei Zhai; Yuhui Zhang (Biomarker Research)
Abstract Background Heart failure (HF) remains a significant public health challenge globally. This study aims to systematically analyze the global HF disease burden from 1990 to 2021 across temporal, spatial, and demographic dimensions to provide evidence for targeted prevention and control strategies. Methods Using data from the Global Burden of Disease (GBD) 2021 study, we analyzed the global HF burden through prevalent cases, years lived with disability (YLDs), and age-standardized rates per 100,000 population. Temporal trends were evaluated using estimated annual percentage change (EAPC) and joinpoint regression analysis. The relationship between the Socio-demographic Index (SDI) and disease burden was explored through Pearson correlation analysis, while attribution analysis identified the main causes of HF. When appropriate, analyses were stratified by 5 SDI regions, 21 GBD regions, 204 countries and territories, 20 age groups, and both sexes. Results Global HF prevalence and YLDs burden showed substantial increases from 1990 to 2021, with age-standardized prevalence increasing from 641.14 to 676.68 per 100,000 population. Notably, high-SDI regions exhibited a declining burden since 2019, indicating a potential global turning point. High-income North America bears the heaviest burden while South Asia shows the fastest growth rate. The correlation between disease burden and SDI level was negligible. The disease burden in males consistently exceeded that in females, with prevalence and YLDs rates rising sharply after age 60. The main causes and their attributable proportions were: ischemic heart disease (34.53%), hypertensive heart disease (22.53%), other cardiomyopathies (7.61%), chronic obstructive pulmonary disease (6.51%), and congenital heart anomalies (5.69%), with their distribution patterns differing across age groups and regions. Conclusion Global burden of HF increased significantly over recent decades, with a potential turning point in 2019 and marked regional disparities. It is essential to prioritize regions with heavy burdens or rapid growth rates, strengthen the management of major causes, and monitor HF burden trends in the post-COVID era.